Control of Cercoseptoria Needle Blight of Pines in Nurseries by Fungicides - Singh, Sujan; Khan, S. N.; Misra, B. M.; Rawat, D. S. (Indian Forester, 1983)
The paper deals with experiments carried out to control Cercoseptoria needle flight of pines in nurseries. Seedlings of Pinus roxburghii, an indigenous pine, and P. greggii, an exotic pine, were used as test species. After screening seven fungicides (dithane M-45, dithane Z-78, cuman L, calixin, bavistin, blitox and karathane) at their prescribed dosages, dithane M-45 and cuman L for P. greggii and dithane Z-78 and calixin along with the above two fungicides for P. roxburghii were selected on the basis of their better performance for testing at higher dosages as none of the seven fungicides effectively controlled the disease at their prescribed dosages. Dithane M-45 and cuman L were found effective at 0.6 per cent concentration in controlling Cercosptoria needle blight on P. greggii in these experiments. On P. roxburghii, however, none of the four fungicides controlled the disease even at highest tested dosages (0.8 per cent except calixin in which case, higher dose was (0.6 per cent). In subsequent experiments where still higher dosages were tested, dithane M-45 and dithane Z-78 effectively controlled the disease on P. roxburghii at 1.0 per cent concentration while in case of calixin the minimal effective dose was found as 0.8 per cent. None of these fungicides had any toxic effect on P. roxburghii seedlings at the higher dosages.